Fiscal divergence, current account divergence and TARGET2 imbalances in the EMU - José Abad; Axel Löffler; Gunther Schnabl; Holger Zemanek (Intereconomics, 2013)
Diverging fiscal policy paths, housing booms and diverging unit labour costs were driving forces of rising intra-European current account imbalances, which were underpinned by low interest rates. Since the outbreak of the crisis, the adjustment of intra-EMU current account imbalances has been postponed by a rising divergence of TARGET2 balances, as the repatriation of private international credit and deposit fl ight from the crisis economies is intermediated by central bank credit. Given that this process has brought the Deutsche Bundesbank into a debtor position to the domestic fi nancial system, the article discusses options for liquidity absorption by the Bundesbank to forestall asset price bubbles in Germany.
Keywords: 330; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Finanzpolitik; Europäische Wirtschafts- und Währungsunion; Internationaler Zahlungsverkehr; Verrechnungsverkehr; Europäische Wirtschafts- und Währungsunion; Geldpolitik